Perlindungan Hukum terhadap Data Pribadi Nasabah Pasca Merger 3 Bank Syariah Menjadi Bank Syariah Indonesia - Shoimah, Siti Nur; Susanti, Dyah Ochtorina (Tapis: Jurnal Penelitian Ilmiah, 2022)
This research was motivated by the merger of three Sharia Banks namely Bank Syariah Mandiri (BSM), Bank Negara Indonesia (BNI) Syariah, and Bank Rakyat Indonesia (BRI) Syariah into Bank Syariah Indonesia. The merger had legal consequences for the customers because the merger policy led to integrating customer personal data into one Big Data. This had become customers' concern related to the security and monitoring system. Consequently, legal protections were needed to secure this issue. This study aims to find a form of legal protection for Sharia Bank Customers after the merger of the three Sharia banks. This study implemented normative legal research with the statute approach and the conceptual approach. The results found that the legal protection for Sharia Bank Customers as intended consists of 2 (two) forms. First, External Protection: legal protection made by the authorities in the form of laws and regulations. Second, Internal protection: legal protection made by the Sharia Bank to secure the customers' personal data.